INTENTION TO BLOOD DONATION: AN EFFECT OF SOCIAL MEDIA - Didik Setyawan; Monica Kristanti; Sugiyarmasto Sugiyarmasto; Abdullah Zailani (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Indonesian people are still reluctant to donate blood. Lack of information and low level of awareness are the causes of this phenomena. Social media has a role in delivering comprehensive information about blood donation. This study aimed at examining the effects of social media in influencing individuals to donate blood. The quality of argumentation, interactive, and social media features can increase the positive attitude to donate blood and to establish blood donation intention. Data collection used were online questionnaire of @sahabatdonordarah Instagram followers as many as 200 respondents. The result of hypothesis testing using the AMOS Structural Equation Modeling analysis showed that the quality of argumentation and interactive social media had an effect on the positive attitude of blood donors in forming blood donation intentions, but it was not for social media features. These results indicated that the quality of the argumentation and interactive social media had a strong role in increasing the positive attitude of donating blood which could influence the intention to donate blood.